TERAPI IMUNOSUPRESAN PADA PASIEN ANEMIA APLASTIK DENGAN PERDARAHAN GUSI: MENYEMBUHKAN ATAU MEMPERPARAH? - Revi Nelonda; Eliza Kristina Munthe; Riani Setiadhi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background: Aplastic anemia (AA) is a hematologic disorder characterized by hypoplastic bone marrow and peripheral pancytopenia. The main symptoms are fatigue and bleeding. In the oral cavity, gingival bleeding is the common complaint.Case Management: A 18-year-old female patient referred from internal medicine department due to swelling of palate since 2 days before that interrupted eating activity. She routinely consumes Sandimun®100 mg tablets. A 2 x 1 cm black blood clot in anterior hard palate and ulcerative lesion at dorsal tongue regio 45 surrounded by necrotic area were found on intra oral examination. Patient was diagnosed with necrotizing ulcer-related neutropenia accompanied by AA-associated hemorrhagic bullae in the hard palate. Patient treated with mouthwash containing 0.1% hyaluronicacid and 1% feracrylum.Discussion: Immunosuppressant is the AA gold standard therapy. Cyclosporine (CsA) as imunosupressant is common drug to prevent T cells from attacking stem cells in bone marrow. The side effects of CsA is gingival hiperplasia.Conclusions: Gingival bleeding and gingival hiperplasia due to thrombocytopenia and the use of cyclosporine are vicious circles that need to be aware. With comprehensive management, good oral conditions will be obtained, therefore the quality of life can increase.